A Study of Frontier and Semifrontier in Intuitionistic Fuzzy Topological Spaces - Athar Kharal (The Scientific World Journal)
Notions of frontier and semifrontier in intuitionistic fuzzy topology have been studied and several of their properties, characterizations, and examples established. Many counter-examples have been presented to point divergences between the IF topology and its classical form. The paper also presents an open problem and one of its weaker forms.